Recruiting intensity - R. Jason Faberman (IZA World of Labor, 2014)
To hire new workers, employers use a variety of recruiting methods in addition to posting a vacancy announcement. The intensity with which employers use these alternative methods can vary widely with a firm's performance and with the business cycle. In fact, persistently low recruiting intensity helps to explain the sluggish pace of US job growth following the Great Recession.
Keywords: E24; J60; 330; hiring; vacancies; recruiting; business cycle; unemployment